Microstructure and mechanical properties of furnace brazed Joints of Inconel 718 with Ni-based filler alloy (BNi-2) - Liu, Cheuk Wing (2018)
Metallurgical joining is a common repair process in the aviation industry involving nickel superalloys such as Inconel 718. However, the high heat input of conventional welding processes frequently induces a heat affected zone (HAZ) on the base metal which detriments the joint’s mechanical strength. As such, researches have been made to develop sophisticated joining processes using advanced filler materials, in view to reduce the effects imposed by HAZ and improve the mechanical properties of the joint. In this study, the effects of brazing parameters such as temperature and soaking duration will be investigated along with the microstructural evolution and mechanical properties of furnaced brazed Inconel 718 with BNi-2 joints. The experiment was designed in a way such that specimens with butt joints were brazed at a constant brazing temperature of 1015℃ with varying soaking durations, while specimens with single lap joints were subjected to brazing at a soaking duration of 60 minutes with varying temperatures. The tensile strength and shear strength, of the butt joint and single lap joint specimens respectively, were evaluated using a universal testing machine, while the microstructures and fracture surface of the joint were analysed using an optical microscope (OM) and scanning electron microscope (SEM). It was found that the butt joint exhibited the highest tensile strength of 340.93MPa corresponding to the longest soaking duration of 60 minutes. Specimens with lap joint had also yielded similar results, proving that the joint strength was directly proportional to the brazing temperature. The microstructure changes of the brazed joint had further proved that the brazing temperature, rather than the soaking duration, has a larger effect on the mechanical strength of the joint. This is mainly attributed by the decrease o brittle hard intermetallic compounds and eutectic constituents such as nickel borides and chromium borides once chemical equilibrium between the base metal and parent material is reached, followed by a homogenization of grains between the base and filler material which contributed to the high mechanical strength of the joint.